Soil biota is decisive for overyielding in intercropping under low phosphorus conditions - Qiao, Xu; Bei, Shuikuan; Wang, Guangzhou; Li, Chunjie; Li, Haigang; Zhang, Junling; Zhang, Fusuo (The Journal of applied ecology, 2022)
Cereal/legume intercropping typically increases crop yield; however, the mechanisms through which soil microbes mediate overyielding in intercropping under different nutrient availability remain elusive. Here we examined the effect of soil biota and phosphate (P) availability on intercropping advantages in wheat Triticum aestivum/faba bean Vicia faba systems using a pot experiment consisting of soil sterilization treatment and different P supply levels. A complementary experiment on the contribution of different microbial groups was also included using the removal method. Intercropping advantage was observed only in the presence of microbes and was mainly associated with increase in wheat biomass. Overyielding effect was stronger under low‐P than high‐P conditions, and was negatively correlated with P availability and the effect of soil biota in the monoculture. The effect was likely related to the enlarged active P pools and modified microbial communities associated with the alteration of rhizosphere traits (protons and carboxylates) by the neighbouring faba bean. Similarly, simplification of soil microbes significantly increased the growth and P uptake of wheat plants while faba bean growth was less affected. Synthesis and applications. Our research provides compelling evidence that soil microbiome is important in driving intercropping overyielding by regulating interspecific interactions under nutrient‐limited conditions. These findings have important implications for crop species choice in designing and managing intercropping systems where crop functional traits, soil microbiome and nutrient management should be integrated in pursuit of sustainable agriculture. Our research provides compelling evidence that soil microbiome is important in driving intercropping overyielding by regulating interspecific interactions under nutrient‐limited conditions. These findings have important implications for crop species choice in designing and managing intercropping systems where crop functional traits, soil microbiome and nutrient management should be integrated in pursuit of sustainable agriculture.